The degree of abstract and tangible intelligence among primary school students with academic learning difficulties - Case Study- [In Arabic] - Arras, Mohamed; Ounes, Amezian (Milev Journal of Research and Studies, 2022)
This study dealt with three cases of primary school pupils with academic learning difficulties, and our attention focused on one of the most important cognitive aspects and mental processes, which is abstract and concrete intelligence. Between chronological age and developmental age, the researcher used the descriptive approach; this is based on a set of data collection tools such as case studies, observation, interviews, the Al-Zayyat battery for measuring learning difficulties, and the EDEI-R intelligence battery. The study found results, most notably a higher average degree of concrete than abstract intelligence, with a difference between chronological age and developmental age.